2011
DOI: 10.1016/j.bbagen.2011.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Histological and functional renal alterations caused by Bothrops alternatus snake venom: Expression and activity of Na+/K+-ATPase

Abstract: Enhanced Na+/K+-ATPase activity in the early hours after envenoming may attenuate the renal dysfunction associated with venom-induced damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…We observed tubular disruption especially in proximal tubules, necrosis in the glomerular and tubular areas, accumulation of collagen fibers in the necrotic areas, and mononuclear cell infiltration in renal tissue of rats treated with VPA (500 mg/kg/day) for 15 days. We also supported kidney injury findings by showing reduced activity of Na + /K + -ATPase which may indicate reduced renal function (Linardi et al 2011). Previously, it has been speculated that VPA might interact with sodium-dependent cotransporters such as Na + /K + -ATPase (Sirac et al 2011).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…We observed tubular disruption especially in proximal tubules, necrosis in the glomerular and tubular areas, accumulation of collagen fibers in the necrotic areas, and mononuclear cell infiltration in renal tissue of rats treated with VPA (500 mg/kg/day) for 15 days. We also supported kidney injury findings by showing reduced activity of Na + /K + -ATPase which may indicate reduced renal function (Linardi et al 2011). Previously, it has been speculated that VPA might interact with sodium-dependent cotransporters such as Na + /K + -ATPase (Sirac et al 2011).…”
Section: Discussionsupporting
confidence: 86%
“…In addition, the activity of Na + /K + -ATPase was measured as an indicator of kidney injury since reduced activity of this enzyme is thought to be a sign of reduced renal function (Linardi et al 2011). Interestingly, vit U treatment given to intact rats reduced the activity of Na + /K + -ATPase (p<0.001, 3.48±0.23 in intact rats and 1.03±0.39 in Vit U-treated rats).…”
Section: Vit U Pretreatment Prevented Vpa-induced Renal Damagementioning
confidence: 99%
“…Injured proximal tubule cells have alterations in the actin and microtubule cytoskeletal networks that lead to a redistribution of Na + /K + ATPase from the basolateral to the apical membrane, contributing to a decrease in Na + transport and reabsorption (Thadhani et al , 1996). It was reported that FE Na+ and FE K+ also increase in envenomation caused by Bothrops snakes (Boer-Lima et al , 1999; Linardi et al , 2011). Despite the redistribution of Na + /K + ATPase to the apical membrane, Linardi et al (2011) reported an increase in expression and activity of Na + /K + ATPase during envenomation by Bothrops alternatus and suggest that it is a protective mechanism triggered in response to natriuresis with the aim to preserve renal function during acute damage.…”
Section: Discussionmentioning
confidence: 99%
“…Functionally, B. alternatus venom induced oliguria, urine acidification, decreased in glomerular filtration rate and hematuria. Morphologically, the venom caused lobulation of the capillary tufts, dilation of Bowman's capsular space, disruption of renal tubule brush border, and fibrosis around glomeruli and proximal tubules that persisted 7 days after envenomation (Linardi et al, 2011;Mello et al, 2010). Some purified Bothrops toxins are able to reproduce the renal effects obtained with whole venom.…”
Section: Bothrops Venommentioning
confidence: 99%